Valve behavior of the oysters Crassostrea gigas and Ostrea edulis and physicochemical data measured during a one-year semi-controlled experiment testing the in situ impact of artificial light at night - Damien Tran; Audrey Botté; Yannick Geerebaert; Laura Payton (PANGAEA, 2025)
Artificial light at night (ALAN) is a worldwide anthropogenic pressure altering the natural sun- and moonlight cycles, with putative impacts on organisms extquotesingle biological rhythms, physiology, and fitness. Compared to terrestrial organisms, ALAN effects have been little studied in coastal ecosystems, despite their widespread exposure to ALAN. To help fill this gap, as part of the LUCIOLE project, we conducted a one-year in situ semi-controlled study to assess the ALAN impact on Crassostrea gigas and Ostrea edulis, two coastal and sessile oyster species likely exposed to ALAN. The experiment took place in the "île aux oiseaux" (44.7°, -1.18°) in Arcachon Bay (France) from December 2023 to November 2024. The experimental platform consisted of two oyster tables spaced 18 meters apart: one table for the control condition exposed to natural light and one table exposed to a continuous and realistic ALAN intensity (?10-6 μE/cm2/s; ?0.5 lx) using LED strips (white light). 16 individuals of each oyster extquotesingles species were disposed on each table and were immersed underwater throughout the experiment. Their valve behavior was continuously measured during one year using the High-Frequency Non-Invasive (HFNI) valvometry. In addition to the oyster behavior, several physicochemical parameters were continuously measured underwater during the experiment: temperature, water depth, conductivity, salinity, turbidity, sound pressure magnitude, and light irradiance. This compilation of datasets gives an overview of all physicochemical parameters and behavioral data collected during this experiment.